2012
DOI: 10.1016/j.neuron.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan Organizes Axon Guidance Cue Localization and Axonal Pathfinding

Abstract: Precise patterning of axon guidance cue distribution is critical for nervous system development. Using a murine forward genetic screen for novel determinants of axon guidance, we identified B3gnt1 and ISPD as required for the glycosylation of dystroglycan in vivo. Analysis of B3gnt1, ISPD and dystroglycan mutant mice revealed a critical role for glycosylated dystroglycan in the development of several longitudinal axon tracts. Remarkably, the axonal guidance defects observed in B3gnt1, ISPD and dystroglycan mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
217
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(223 citation statements)
references
References 54 publications
5
217
1
Order By: Relevance
“…Slits can also homodimerize; the LRR4 domain is required for this dimerization (Seiradake et al, 2009). Importantly, Slits show additional heterophilic binding to other ECM molecules, including Neurexins, Type IV Collagens (Xiao et al, 2011), Netrin 1 , dystroglycan (Wright et al, 2012), Glypican (Liang et al, 1999) and Syndecan (Johnson et al, 2004;Steigemann et al, 2004).…”
Section: Slit Ligands and Robo Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Slits can also homodimerize; the LRR4 domain is required for this dimerization (Seiradake et al, 2009). Importantly, Slits show additional heterophilic binding to other ECM molecules, including Neurexins, Type IV Collagens (Xiao et al, 2011), Netrin 1 , dystroglycan (Wright et al, 2012), Glypican (Liang et al, 1999) and Syndecan (Johnson et al, 2004;Steigemann et al, 2004).…”
Section: Slit Ligands and Robo Receptorsmentioning
confidence: 99%
“…Slit-C was recently shown to bind plexin A1 and to induce growth cone collapse of mouse spinal cord commissural axons (DelloyeBourgeois et al, 2014). In addition, Slit-C binds to the basement membrane scaffolding protein dystroglycan (Wright et al, 2012).…”
Section: The Proteolytic Processing Of Robo and Slitsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-DG docks with transmembrane β-DG to form the functional core of the dystrophinassociated glycoprotein complex (DGC) that links adhesive proteins in the extracellular matrix to dystrophin (5). α-DG is heavily glycosylated and interacts via its carbohydrate side chains with laminin and laminin G-like domains in a variety of proteins including agrin, perlecan, slit, neurexin, and pikachurin (6)(7)(8)(9)(10). Key carbohydrate residues are added onto α-DG by several glycosyltransferases, most notably like-acetylglucosaminyltransferase (LARGE) (11).…”
mentioning
confidence: 99%
“…␤3GnT1, which is involved in the synthesis of poly-N-acetyllactosamine (18) and whose sequence is closely related to the second domain of LARGE (19), has been shown to contribute to the synthesis of the laminin-binding glycan of ␣-DG through formation of a complex with LARGE (20). Moreover, a study using a forward genetic screen demonstrated that ␤3GnT1 is required for functional glycosylation of ␣-DG in vivo; mice expressing a mutant form of this protein exhibited axonal-guidance defects like those observed in ISPD or an epiblast-specific DG mutant mouse (21). Recently, SGK196 was found to be a protein O-mannose kinase (designated as POMK) that generates [GalNAc-␤3-GlcNAc-␤4-(phosphate-6-)Man], a modification required for the functional glycosylation of ␣-DG (22).…”
mentioning
confidence: 99%